Membangun Kerukunan Antar Umat Beragama Agar Terciptanya Perdamaian Di Tengah-Tengah Masyarakat Pada Masa Kini (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This article discusses the development of harmonious living between religious communities in order to create peace in society. The country of Indonesia indeed consists of various diversity starting from ethnicity, culture, ethnicity, religion. However, behind this diversity, various conflicts between religious communities have emerged. However, looking at the conflicts that occur in the current era, society has become divided among itself. To be able to realize peace between religious communities is an effort to restore the essence of religion and foster an attitude of tolerance and living in harmony. Tolerance plays an important role in building society and harmony is a condition where a person or group lives together peacefully, harmoniously and with mutual respect for each other. Harmony involves mutual understanding, tolerance, and the ability to resolve conflicts in a peaceful manner. Peace between religious communities is an important aspect in creating a peaceful and just world. This effort involves all parties working together to achieve the common goal of creating harmony between religious communities. The main goal of peace between religious communities is to overcome differences in religious beliefs and practices to build an inclusive and tolerant society. The concepts of harmony and tolerance are often the basis for creating a balanced and sustainable social life. Harmony is very important to create a peaceful and thriving environment.